Predictive power of oil prices on CDS spread dynamics of oil-producing countries - Christoph Wegener; Tobias Basse; Stefano Maiani; Tam Huu Nguyen (Heriot-Watt University, Department of Accountancy, Economics, and Finance, 2025)
This paper employs predictive regressions to explore the predictability of sovereign Credit Default Swap (CDS) spread dynamics of relevant oil-producing countries. By incorporating oil prices and additional control variables, we predict the rate of CDS spread changes for Brazil, the UK, Malaysia, Norway, Qatar, Russia, Saudi Arabia, the US, and Venezuela. Our findings reveal that (i) the empirical coefficients of determination (R 2 ) indicate low in-sample predictability for our entire period of analysis (2010-2024), the R 2 increases markedly when dividing the analysis period into more relevant sub-samples (2010-2016 and 2016-2024); (ii) oil prices are not significant predictors for the full period but become significant in many regressions within sub-samples; (iii) for countries where oil prices are significant in both sub-samples, the coefficient sign changes from negative to positive, suggesting that in more recent years, rising (falling) oil prices signal increasing (decreasing) geopolitical risk, positively (negatively) influencing CDS spreads.
Keywords: G17; H63; C58; Q43; 330; oil prices; fiscal stability; predictive regressions